Perencanaan Dan Perancangan Pusat Kreatif Masyarakat â€œKlungkung Creative Centerâ€ Di Kabupaten Klungkung: Bahasa Indonesia - I Kadek Udayana; I Putu Hartawan; I Ketut Sugihantara (Undagi : Jurnal Ilmiah Jurusan Arsitektur Universitas Warmadewa, 2023)
Poverty and unemployment in Bali, especially in Klungkung Regency, have experienced a significant increase over the past three years due to the Covid-19 pandemic. The poverty rate in Bali increased from 3.61% in 2019 to 4.72% in 2021, while the unemployment rate in Klungkung increased from 1.57% in 2019 to 5.37% in 2021, making it the fifth highest region with unemployment in Bali. To address the issue of unemployment and poverty in Klungkung Regency, it is necessary to build facilities that can help develop the creative industry and advance the economy. Therefore, a community creative center called "Klungkung Creative Center" has been designed to function as a center for creativity and creative industry development. This facility will be equipped with rooms and facilities that can be used by the people of Klungkung, such as a business incubation center, creative center, co-working space, and makerspace. The users of this facility are divided into several groups, namely managers, students, creative economy actors, communities, and the general public. Architecture plays a crucial role in creating adequate conditions and infrastructure for the people of Klungkung to enhance their economic potential and creativity. It is expected that with this facility, the people of Klungkung and surrounding areas can improve their skills, knowledge, and creativity while advancing their achievements, economy, and tourism in the region.